Upaya Penghijauan Melalui Dakwah Peduli Lingkungan Hidup Di Desa Sambirejo - Tanjung, Lidra Agustina; Prandana, Arya; Kharomah, Larasati Nur; Salsabila, Salsabila (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Activity with the theme "Da'wah Cares for the Environment" aims to increase public awareness of the importance of protecting the environment through a religious approach. The methods include outreach through social media and leaflets, da'wah through lectures, studies and thematic discussions in mosques, prayer rooms and religious associations, as well as real action in the form of greening in public areas.The results show an increase in enthusiasm and public understanding regarding the importance of protecting the environment. The community actively participates in reforestation activities, even forming self-help plant care groups. Supporting factors for the success of are collaboration with religious and community leaders, effective use of media, and preaching material that is easy to understand. Inhibiting factors include limited resources and regional coverage. However, this program has had a significant positive impact on Sambirejo Village, creating a greener environment, increasing public awareness, and fostering a sense of ownership of the environment. It is hoped that this activity can become a model for other regions in religious-based environmental conservation efforts.